(3TQM GdgOGjI GdCKjQjIs - (3eMeO Hf MSjf GdeOYh HaNQ GdOjf GdMSjfjs; (3ceGd GdOjf MSjf GdeHJOFs
(3ChdgG (B:s
(3GdMeO ddg GdYdje GdMcje hHYO ajbhd Cf CTQM GdgOGjg GdCKjQjg ddaGVd ceGd GdOjf MSjf bGd GYde Cf GdMceg Yde s
(3BNQgG (B:s
(3hJhVjM GdcdGe Cf GdUhQI GdLSejI fXQ Edi faSgG eY bWY GdfXQ Yf GdCehQ GdNGQLI GeG Cf dG Jchf eMJGLg Edi eMd hMQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs